Positive Healthy Organizations: Promoting Well-Being, Meaningfulness, and Sustainability in Organizations - Di Fabio, Annamaria (Frontiers in Psychology, 2017)
This contribution deals with the concept of healthy organizations and starts with a definition of healthy organizations and healthy business. In healthy organizations, culture, climate, and practices create an environment conducive to employee health and safety as well as organizational effectiveness (Lowe, 2010). A healthy organization thus leads to a healthy and successful business (De Smet, Loch, & Schaninger, 2007; Grawitch & Ballard, 2016), underlining the strong link between organizational profitability and workers’ well-being. Starting from a positive perspective focused on success and excellence, the contribution describes how positive organizational health psychology evolved from occupational health psychology to positive occupational health psychology stressing the importance of a primary preventive approach. The focus is not on deficiency and failure but on a positive organizational attitude that proposes interventions at different levels: individual, group, organization, and inter-organization. Healthy organizations need to find the right balance between their particular situation, sector, and culture, highlighting the importance of well-being and sustainability. This contribution discusses also the sustainability of work-life projects and the meaning of work in healthy organizations, stressing the importance of recognizing, respecting, and using the meaning of work as a key for growth and success. Finally, the contribution discusses new research and intervention opportunities for healthy organizations.